2013
DOI: 10.1080/14786419.2012.695363
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and leishmanicidal properties of garcinielliptone FC, a prenylated benzophenone fromPlatonia insignis

Abstract: Garcinielliptone FC (GFC), a natural prenylated benzophenone, was extracted from Platonia insignis Mart. (Clusiaceae), a native plant commonly known as bacuri and used in traditional Brazilian medicine for the treatment of skin diseases. The aim of this study was to evaluate the cytotoxic and leishmanicidal effects of GFC using in vitro models. The experimental data demonstrated that the polyisoprenylated benzophenone GFC possesses cytotoxic and leishmanicidal activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 16 publications
1
15
0
5
Order By: Relevance
“…In turn, GFC 20 and 30 lg/mL induced cell viability below 70% after exposure for 6 and 24 hr. The results of the present study confirm the findings published in a previous study [19], when GFC 25 lg/mL was shown to inhibit growth of NCI-H292 cells (mucoepidermoid carcinoma in human lung) by approximately 88% in the MTT test after 72 hr of exposure. Other benzophenones, such as 2,2 0 ,5,6 0 -tetrahydroxybenzophenone, isogarcinol, isoxanthochymol and guttiferone E, have been shown to be cytotoxic to the HCT116 colon carcinoma and leukaemia CCRF cell lines [37].…”
Section: Discussionsupporting
confidence: 92%
“…In turn, GFC 20 and 30 lg/mL induced cell viability below 70% after exposure for 6 and 24 hr. The results of the present study confirm the findings published in a previous study [19], when GFC 25 lg/mL was shown to inhibit growth of NCI-H292 cells (mucoepidermoid carcinoma in human lung) by approximately 88% in the MTT test after 72 hr of exposure. Other benzophenones, such as 2,2 0 ,5,6 0 -tetrahydroxybenzophenone, isogarcinol, isoxanthochymol and guttiferone E, have been shown to be cytotoxic to the HCT116 colon carcinoma and leukaemia CCRF cell lines [37].…”
Section: Discussionsupporting
confidence: 92%
“…Its fruits are known for their pleasant taste and aroma and are highly appreciated by the Amazonian people [15]. Some studies have reported the biological activity of different extracts of P. insignis and the chemical components, such as Garcinielliptone FC, responsible for the biological activity, have already been isolated and identified [12,13,16]. However, the ethnopharmacological use of P. insignis is related to the use of the extracts of its seeds, bark, or fruit pulp because of its ability to heal, anti-inflammatory effects, leishmanicidal agents, antioxidants, and cytotoxic activities.…”
Section: Discussionmentioning
confidence: 99%
“…Native to the Brazilian Amazon forests, P. insignis is a fruit-bearing and woody plant with a dense and diverse distribution throughout the country [11]. Traditionally, it has been used to treat various ailments related to the digestive tract and rapid wound healing, and was also reported to have diuretic and antitumor properties [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The species P. insignis cannot be considered an herbal yet, but the GFC isolated from the hexane extract of its seeds has been used in various experimental protocols and has demonstrated several biological properties such as anti-inflammatory [28], antioxidant [1,29], antileishmanial, cytotoxic [30] and vasorelaxing properties in rat mesenteric artery [31]. These data and the present study are useful to provide more information to strengthen the rational therapy and safety margins of pharmaceutical, cosmetic and/or food products originated from this species, such as, folk juices, ice creams, jellies, among others by the Brazilian Northeast population.…”
Section: Discussionmentioning
confidence: 99%